Hak Asasi Alam: Mempertimbangkan Conatus Essendi dalam Perspektif Materialisme Baru - Kaho, Eventus Ombri (Sanata Dharma University, 2025)
This study examines the concept of natural rights through the lens of discourse analysis, focusing on how Baruch Spinoza’s idea of conatus essendi is reinterpreted within the framework of new materialism. Traditionally, natural rights have often been confined to the anthropocentric realm, ignoring the existence and agency of non-human entities. However, the emergence of the discourse of natural rights demands a paradigm shift, encouraging the recognition of the intrinsic rights of nature. Using a discourse analysis approach, this study seeks to examine how arguments and narratives supporting natural rights are constructed and contested in various texts, such as scientific publications, policy statements, and environmental activist manifestos. Specifically, the study attempts to trace Spinoza’s conatus essendi, the innate tendency of every entity to continue to exist and perpetuate itself, within the discourse of new materialism. New materialism offers a philosophical foundation that allows for the expansion of the subject’s rights, transcending the boundaries of humanity and recognizing the interconnectedness and agency of matter. Thus, this study not only highlights the ontological shift in the understanding of rights but also reveals the transformative potential of new materialism in reshaping the relationship between humans and nature. The results of this research are expected to contribute to the development of a more inclusive and sustainable human rights theory.